Kesetaraan Gender Perspektif Kosmologi Islam - Muhammad Taufiq (Tasfiyah: Jurnal Pemikiran Islam, 2018)
On Ibn ‘Arabi’s view, both man and woman were created to be able to represent cosmic entity, even more they are manifestations of Allah’s attributes considering His Jalal (Greatness) and Jamal (Beauty). Lately, the people have been preoccupied by various gender issues promoted by feminist activists. They criticize on the relationship between men and women arranged by the Islamic religion that it harms the law and the equality. This movement continues to influence Muslims’ lives and thoughts through education, technology, and any discussions held. Therefore, this article could counter their accusation toward Islam and could prove that they are wrong. It is because Islam has a very good order in regulating relationship between men and women to maintain the stability of human life.